Properties of different varieties of Maranta arundinacea’s starch. - Cunha, Amanda Logato; Andrade, Luan Alberto; Silva, Ana Caroline; Pereira, Joelma (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2022)
The objective of this study was to analyze and compare arrowroot starch varieties of the "seta" (AS) and "redonda" (AR) varieties by assessing their chemical, morphological, rheological, structural and thermal characteristics, and verifying their applicability in the food industry. This research involved: proximal composition (moisture, ether extract, crude protein, crude fiber, ashes and glicidic fraction), infrared spectroscopy, scanning electron microscopy, determination of paste clarity and properties, X-ray diffraction, and thermal properties. The extracted starches have high purity, having low levels of the components analyzed in the proximal composition. The main chemical groups found in polysaccharides were determined in infrared spectroscopy. Both arrowroot starches exhibited fragility to high temperatures, lower resistance to dissociation of hydrogen bonds, and high final viscosity. The characteristic size of the starch granules is in the range of 8 μm to 45 μm, with a predominance of granules of approximately 30 μm, for both AR and AS, which can be considered large granules. The granules predominant geometric shapes are oval and ellipsoid Starches exhibited type-C crystallinity and initial, peak and final temperature values for gelatinization were well below the temperatures found in literature. The two starches exhibited potential for use in the industry of instant foods, breakfast cereals, infant food, meat products, and bakery products.